High‐coverage proteomics reveals methionine auxotrophy in Deinococcus radiodurans. Issue 13 (July 2017) - Zhou, Yanxia; Shen, Pan; Lan, Qiuyan; Deng, Chen; Zhang, Yao; Li, Yanchang; Wei, Wei; Wang, Yihao; Su, Na; He, Fuchu; Xie, Qiong; Lyu, Zhitang; et al.
Abstract : Deinococcus radiodurans is a robust bacterium best known for its capacity to resist to radiation. In this study, the SDS‐PAGE coupled with high‐precision LC‐MS/MS was used to study the D. radiodurans proteome. A total of 1951 proteins were identified which covers 63.18% protein‐coding genes. Comparison of the identified proteins to the key enzymes in amino acid biosyntheses from KEGG database showed the methionine biosynthesis module is incomplete while other amino acid biosynthesis modules are complete, which indicated methionine auxotrophy in D. radiodurans . The subsequent amino acid‐auxotrophic screening has verified methionine instead of other amino acids is essential for the growth of D. radiodurans . With molecular evolutionary genetic analysis, we found the divergence in methionine biosynthesis during the evolution of the common ancestor of bacteria. We also found D. radiodurans lost the power of synthesizing methionine because of the missing metA and metX in two types of methionine biosyntheses. For the first time, this study used high‐coverage proteome analysis to identify D. radiodurans amino acid auxotrophy, which provides the important reference for the development of quantitative proteomics analysis using stable isotope labeling in metabolomics of D. radiodurans and in‐depth analysis of the molecular mechanism of radiation resistance.